Bone support of the foot: anatomy and variability of the calcaneus - Hryn , V.H.; Tikhonova , O.O.; Tarasenko , Ya.A.; Bilash , V.P.; Severyn , Yu.M.; Strizhenok , V.P.; Gorobets , O.V. (Морфологія / Morphologia / Morfologìâ, 2025)
Background. The key element of the musculoskeletal system in terms of load distribution, ensuring foot stability, and forming its arch is the calcaneus. Therefore, the study of the anatomical features of the calcaneus is important both for fundamental morphology and for clinical practice, podiatry and forensic medical examination. Objective is to analyze the anatomical, morphological and functional features of the calcaneus, its variability and clinical significance. Methods. An analytical review was used, which is based on foreign and domestic articles, books and monographs. For this purpose, the literature search was carried out on the Internet, scientific and metric databases. The search period was conducted until 2025. Results. The configuration of the articular surfaces of the calcaneus demonstrates significant anatomical variability, which has not been considered functionally important for a long time. Anatomically, the calcaneus consists of spongy tissue with a thin cortical shell. However, in certain areas, the cortical layer is significantly thickened. The calcaneus has well-developed vascularization. which provides growth and healing in injuries. Morphological variability of the articular surfaces can affect the biomechanics of the foot and has ethnic differences, which confirms its genetic determination. Conclusion. In conclusion, the calcaneus plays a crucial role in the biomechanics of the foot, providing stability to the subtalar joint, distributing weight, and adapting to mechanical loads. The structural features of the calcaneus make it key in supporting the foot’s arch and performing motor functions. Surgical interventions must consider the specifics of its anatomy and vascular network to prevent ischemic complications. Radiological parameters are important diagnostic criteria for evaluating fractures and degenerative changes, and the presence of spurs often indicates pathological processes diagnostic criteria in the assessment of fractures and degenerative changes, and the presence of spurs often indicates pathological processes.